Factors associated with adverse outcomes during influenza outbreaks in aged care facilities. (16th October 2019) - Tennant, Elaine; Fletcher, Stephanie; Kakar, Sheena; Najjar, Zeina; Lord, Heidi; Clark, Penelope; Gupta, Leena
Abstract: Objective : To explore factors associated with adverse outcomes during influenza outbreaks in residential aged care facilities. Methods : A retrospective cohort study of all outbreaks reported to three Sydney metropolitan Public Health Units during 2017. Results : A total of 123 outbreaks affected 1, 787 residents and 543 staff. Early notification to a Public Health Unit was associated with shorter outbreak duration ( p <0.001; B=0.674). Resident attack rates and resident mortality rates were lower in outbreaks notified early, on univariate analysis ( p= 0.034 and p= 0.048 respectively) but not on an adjusted model. Staff attack rates were significantly associated with resident attack rates ( p= 0.001; B=0.736). Data on staff vaccination rates was incomplete and reported coverage rates were low (median 39%). Resident vaccination coverage ≥95% was associated with shorter outbreak duration in univariate testing but not on an adjusted model. Conclusions : Early public health notification is associated with improved outbreak parameters; sick staff may pose a risk to residents, yet vaccination rates are low. Resident vaccination may also be valuable. Implications for public health : Measures that facilitate early PHU involvement in influenza outbreaks should be implemented, such as compulsory reporting requirements and processes that permit easier notification through technology. Actions that enhance staff and resident vaccination coverage should also be undertaken.